2002
DOI: 10.1002/xrs.561
|View full text |Cite
|
Sign up to set email alerts
|

Determination of oxidation states of aluminium, silicon and sulfur

Abstract: The lines of the emission spectra originating from vacancies in deep atomic shells change if the elements are in different oxidation states. These changes are shown in this paper, and also the influence that they may have on the calibration of wavelength-dispersive spectrometers and, in consequence, on quantitative analysis by XRF or EPMA. Also, these changes prove to be useful in identifying and, in some cases, quantifying phases in different oxidation states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…[4,5] ). Selective determination of particular oxidation states by WD-XRF has been reported not only for sulphur [6] but also for aluminium and silicon [5] , iron [7] and chromium. [8] However, most effort seems to have been made to optimise calibrations for total element analysis and to overcome the 'mineralogical effect'.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,5] ). Selective determination of particular oxidation states by WD-XRF has been reported not only for sulphur [6] but also for aluminium and silicon [5] , iron [7] and chromium. [8] However, most effort seems to have been made to optimise calibrations for total element analysis and to overcome the 'mineralogical effect'.…”
Section: Introductionmentioning
confidence: 99%
“…The second vacancy leads to deviant, typically increased energy levels and, consequently, results in shorter wavelengths of the associated fluorescence radiation. [6] However, sulphur is characterised by low energy satellites, [11] which are of particular interest because their occurrence is distinctly promoted along with higher oxidation states and the presence of oxygen as sulphur ligand in complex sulphur anions. [6] Thus, satellite lines appear in XRF spectra of specimen containing sulphates rather than sulphides.…”
Section: Introductionmentioning
confidence: 99%
“…The main difference between the Kb spectra from pure elements and from their compounds is the presence of a satellite line, Kb 0 , of lower energy, that is directly related with the chemical nature of the ligand [4]. It has also been observed that the Kb 1,3 principal peak in the spectra of oxidized compounds becomes more symmetrical and shifts towards lower values of energy [5]. The symmetry increase in the compounds with light ligands such as C, N, O and F, may be due to the formation of covalent bonds strongly localized, a behavior opposed to that of the characteristic bond of metals.…”
Section: Introductionmentioning
confidence: 92%
“…Similarly as for the absorption spectrum the chemical environment of an element affects and modifies also the various characteristics of its x-ray emission spectrum. Usually, the influence of the chemical environment results in energy shifts of the characteristic lines, formation of satellite lines and changes in the emission linewidths and relative intensities (Gohshi et al 1973, Perino et al 2002, Tamaki 1995, Yasuda et al 1978. A very important qualitative difference with the XAS spectroscopy requiring synchrotron source is that the xray emission spectrum can be recorded also in a smaller laboratory employing an x-ray tube (XRF) or proton accelerator (PIXE) in combination with wavelength dispersive x-ray spectrometer.…”
Section: Chemical Speciation Of Light Elements Via High Resolution X-mentioning
confidence: 99%
“…The high resolution K emission measurements probes directly the p-density of occupied valence states and should therefore reflect with higher sensitivity the chemical environment of element in the sample. In fact most of the experimental as well as theoretical work on the chemical speciation of light elements, such as sulfur, has been focused on K emission measurements (Kavčič et al 2007, Maeda et al 1998, Perino et al 2002, Sugiura et al 1974, Uda et al 1999. All these works show pronounced effects in the emitted K x-ray spectra, however, in contrast with the K spectra exhibiting independent characteristic lineshape the measured K spectra are much more complex and consequently it is very difficult to give a simple parameter as it was the energy shift in the case of K spectra, which would correlate directly with the oxidation state and enable simple, reliable identification of the latter.…”
Section: Chemical and Structural Analysis Of Light Elements Via High mentioning
confidence: 99%